Strategies to Assist Distance Doctoral Students in Completing Their Dissertations - Lim, Janine; Covrig, Duane; Freed, Shirley; De Oliveira, Becky; Ongo, Mordekai; Newman, Isadore (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
Completing doctoral dissertations is difficult work and may be harder for distance students physically separated from institutional and collegial supports. Inability to complete independent research contributes to doctoral student attrition. Factors impacting completion include institutional factors, student characteristics, and supervisory arrangements (Manathunga, 2005). This paper shares proactive strategies used by a Midwestern university in the United States to support distance doctoral students. Strategies and technology tools are described that (a) cultivate a shared culture of responsibility and commitment, (b) increase effective communication between researchers, and (c) grow departmental and institutional services and technologies for faculty and students. This paper suggests the use of a specific framework to help students develop a shared culture of responsibility. This framework encourages students to discuss their social network, as well as teaches students how to manage their split life by using a tool which evaluates a student’s readiness for the dissertation process and maps out where dissertation skills and knowledge are developed throughout the program. Strategies for effective communication include availability, effective feedback, trust, and humor. Services and technologies provided to build capacity include the use of online and library resources, campus-wide use of research software, writing and research services, and department supports and processes to promote student research. These mechanisms for accountability, mentoring, training, and trust increase the likelihood of success.